Respostas

2013-11-25T17:05:19-02:00
3x - y = 10
x + y = 18

x = 18 - y
3 (18 - y) - y = 10
54 - 3y - y = 10
- 3y - y = 10 - 54
- 4y = - 44
y = - 44 ÷ (- 4)
y = 11
Vamos encontrar o valor de x:
x = 18 - y
x = 18 - 11
x = 7

Resposta:
x = 7
y = 11
  • Usuário do Brainly
2013-11-25T17:11:14-02:00
3x - y = 10
x + y = 18

- y = 10 - 3x
y = - 10 + 3x

x + (- 10 + 3x) = 18
x - 10 + 3x = 18
x + 3x = 18 + 10
4x = 28
x = 28 : 4
x = 7
Valor de y:
y = - 10 + 3x
y = - 10 + 3 * 7 
y = - 10 + 21
y = 11
S: {x = 7; y = 11}